Pengaruh Penerapan E-Audit dan Etika Auditor terhadap Kualitas Audit dengan Time Budget Pressure sebagai Pemoderasi - Priscilla, Tiara Victoria; Arsjah, Regina Jansen (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to examine and analyze the impact of e-audit implementation and auditor ethics on audit quality, with time budget pressure as a moderator. The research sample consists of auditors working at public accounting firms (KAP) in the Jakarta area. The sampling method employed was purposive sampling, yielding 110 respondents who completed a questionnaire distributed via Google Forms. The data collected were primary data analyzed using multiple linear regression. The research results show that the implementation of e-audit has a positive effect on audit quality. Meanwhile, auditor ethics and time budget pressure have a negative effect on audit quality. Time budget pressure has two different effects, namely worsening the positive effect of implementing e-audit on audit quality, but strengthening the positive effect of auditor ethics on audit quality.